2014
DOI: 10.1101/004325
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Behavioral variation in Drosophila melanogaster: no evidence for common alleles of large- effect at the foraging gene in a population from North Carolina, USA

Abstract: It has been postulated that natural populations of Drosophila melanogaster are comprised of two behavioral morphs termed "rover" and "sitter", and that this variation is caused mainly by largeeffect alleles at a single locus. Contrary to common assertions, however, published support for the existence of common large effect alleles in nature is quite limited. To further investigate, we quantified the foraging behavior of 36 sequenced strains from a natural population, performed an association study, and describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…To the best of our knowledge, our study is the first effort to identify the genetic basis underlying Drosophila adult foraging behavioral variation on a genomic scale, which is critical for understanding the genetic divergence that leads to evolution of adult foraging behavior among species, such as those observed previously ( Chen et al 2012 ). Natural variation in foraging behavior has been surveyed in Drosophila larvae ( Sokolowski 1980 ; Bauer and Sokolowski 1984 ; Sokolowski et al 1997 ), and studies have linked that the phenotypic variation to a single locus ( for , Belle et al 1989; Sokolowski et al 1997 ; Sokolowski 2001 , but see Turner et al 2015 ). There, it is commonly taken that larval foraging behavior depends mainly on large-effect alleles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, our study is the first effort to identify the genetic basis underlying Drosophila adult foraging behavioral variation on a genomic scale, which is critical for understanding the genetic divergence that leads to evolution of adult foraging behavior among species, such as those observed previously ( Chen et al 2012 ). Natural variation in foraging behavior has been surveyed in Drosophila larvae ( Sokolowski 1980 ; Bauer and Sokolowski 1984 ; Sokolowski et al 1997 ), and studies have linked that the phenotypic variation to a single locus ( for , Belle et al 1989; Sokolowski et al 1997 ; Sokolowski 2001 , but see Turner et al 2015 ). There, it is commonly taken that larval foraging behavior depends mainly on large-effect alleles.…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila , variation at a single locus ( foraging ) was suggested as the sole contributor to bimodal variation in larval foraging behavior in wild populations (“rover” vs. “sitter”, Belle et al 1989 ; Osborne et al 1997 ; and reviewed in Sokolowski 2001 , but see Turner et al 2015 ). However, unlike larvae, adult flies are intermittent eaters and their foraging behaviors are expected to be much more complex ( Masek et al 2014 ; Qi et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of the rover-sitter variants, a mechanism known as balancing selection could explain the maintenance of these variants if they are exposed to NPP heterogeneity in space and time. Although this mechanism seems plausible in Drosophila, a recent study suggested that strong balancing selection at the for gene beginning recently (i.e., following migration out of Africa) is unlikely (Turner et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the rover-sitter variants, a mech-anism known as balancing selection could explain the maintenance of these variants if they are exposed to environmental heterogeneity. Although this mechanism seems plausible in Drosophila, a recent study suggested that strong balancing selection at the for gene beginning recently (i.e., following migration out of Africa) is unlikely (Turner et al, 2015). The effect of precipitation as a spatially selective force could not be ruled out though, as the balancing selection test performed by the authors was based on a lineage-specific McDonald-Kreitman model, which does not consider the effect of the environment.…”
Section: Discussionmentioning
confidence: 99%